The Enabling Electronic Motif for Topological Insulation in ABO3 Perovskites. (7th August 2017) - Zhang, Xiuwen; Abdalla, Leonardo B.; Liu, Qihang; Zunger, Alex
Abstract : Stable oxide topological insulators (TIs) have been sought for years, but none have been found; whereas heavier (selenides, tellurides) chalcogenides can be TIs. The basic contradiction between topological insulation and thermodynamic stability is pointed out, offering a narrow window of opportunity. The electronic motif is first identified and can achieve topological band inversion in ABO3 as a lone‐pair, electron‐rich B atom (e.g., Te, I, Bi) at the octahedral site. Then, twelve ABO3 compounds are designed in the assumed cubic perovskite structure, which satisfy this electronic motif and are indeed found by density function theory calculations to be TIs. Next, it is illustrated that poorly screened ionic oxides with large inversion energies undergo energy‐lowering atomic distortions that destabilize the cubic TI phase and remove band inversion. The coexistence windows of topological band inversion and structure stability can nevertheless be expanded under moderate pressures (15 and 35 GPa, respectively, for BaTeO3 and RbIO3 ). This study traces the principles needed to design stable oxide topological insulators at ambient pressures as a) a search for oxides with small inversion energies; b) design of large inversion‐energy oxide TIs that can be stabilized by pressure; and c) a search for covalent oxides where TI‐removing atomic displacements can be effectively screened out. Abstract : ABO3 perovskites where B is an electron‐rich element would be topological insulators if the cubic structure could be stabilized. But in such band‐inverted topological insulators, depopulation of bonding valence states and occupation of antibonding conduction states raises the energy, leading, in some cases, to structural distortions that are poorly shielded in oxides. In the distorted structure the band inversion is reversed.